Innovative approaches to agricultural water use for improving food security in sub-Saharan Africa - Inocencio, A. (International Water Management Institute, 2003)
The aim of this paper is to discuss how innovative approaches to agricultural water use could contribute to alleviating food insecurity and poverty in SSA in a sustainable way.